Below the Glass Floor : Analytical Review of Expenditure by Provincial Administrations on Rural Health from Health Function Grants and Provincial Internal Revenue - World Bank (Washington, DC, 2014)
Below the glass floor is a report that explores the impact of recent increases in operational function grant funding to provinces to support rural health service delivery. It seeks to identify what expenditure provinces have made to support and enable key front line service delivery activities such as; facility operations, patrols, medical supply distribution, emergency patient transfer, rural water supply and facility supervision. This top down trend analysis seeks to identify whether spending has been made in these areas as a first step in understanding the effectiveness of the governments' financial arrangements. The next step is to triangulate the findings using field-based research that assesses what impact the funding is having at the facility level.